Pembuatan Papan Nama Posyandu di Blok V RW 10 - Tania, Celine; Jesclin, Jesclin; Sutini, Sutini; Jesen, Jesen; Bryan, Bryan; Frankie, Frankie (National Conference for Community Service Project (NaCosPro), 2019)
Implementation of Sepora conducted in Blok V RW 10 Batu Selicin was motived by a lack of facilities Posyandu facilities and the importance of Posyandu for the community to receive and obtain health services well and satisfactorily. The method is making the nameplate of Posyandu. the aim is to better introduce the community to the existence of a Posyandu in the surrounding environment and encourage the community to visit the Posyandu. The result of implementation received a fairly good response and the community also became more aware of the importance of the Posyandu